Obstetrics and Gynecology Emergency Department Activity during Lockdown in a Teaching Hospital, Hub Center, for COVID-19. (5th September 2022) - Amadori, R.; Buscemi, R.; Desando, A.; Grillo, F.; Remorgida, V.; Surico, D.
Abstract : Background . The lockdown related to the SARS-CoV-2 pandemic has imposed profound changes in the interaction of the population with hospitals and emergency departments. The main aim of this research was to evaluate the impact of lockdown on the activity of obstetrics and gynecology emergency department (OGED) in a teaching hospital, hub center, for COVID-19. Methods . The study considers all visits to the OGED with their different triage color codes that represent the clinical severity of each case (from the most severe to the least one: red, yellow, green, white). Data were selected through the "PSNet" triage program and collected anonymously. We analyzed frequency distributions of the variables separately for each woman and calculated mean and standard deviations for continuous variables. We then analyzed the association between factors and outcomes for categorical variables (expressed as a number and percentage of the total) using the chi-square test ( χ 2). The level of significance was established with p < 0.05 . Statistical analysis was performed using SPSS Statistics V20.0. Given the fact that the study has a retrospective observational nature and it is based on an anonymous routine database, approval by the Local Ethics Committee was not necessary. Results . The relative decrease of patients presenting to OGED in 2020 was −50.96%. The percentage of nonpregnant women was significantly lower in 2020 compared to 2019 (p ≤ 0.0001 ; Δ = −79.46%). Regarding the obstetric group, we saw an important decrease of visits in 2020 compared to 2019 (p < 0.0001 ; Δ = −40%). The prevalence of yellow codes was significantly higher in 2020 (Δ = +29.72%), while that of white (Δ = −61.58%) and green (Δ = −52.22%) codes was significantly lower (p ≤ 0.0001 ). Comparing the diagnoses at discharge, we could highlight significant reductions in 2020 for more than one diagnosis: bleeding (p ≤ 0.0001 ; Δ = −70.42%), pain (p ≤ 0.0001 ; Δ = −81.22%), urinary diseases (p = 0.004 ; Δ = −75.64%), and gastrointestinal diseases (p ≤ 0.0001 ; Δ = −87.50%). Conclusions . An evident change emerged in relation to the dynamics between the local obstetrical and gynecological population, and OGED resources. The COVID‐19 lockdown greatly reduced the rate of admission to OGED without time-related obstetric and gynecological complications. The reduction of admissions suggests a more appropriate use of the ED by patients that may inspire future policies for the implementation of emergency services.